Bacteria peptidoglycan promoted breast cancer cell invasiveness and adhesiveness by targeting toll-like receptor 2 in the cancer cells. - Wenjie Xie (Public Library of Science (PLoS), 2010)
Chronic bacterial infection increased the risk of many solid malignancies and the underlying mechanism is usually ascribed to bacterial-caused inflammation. However, the direct interaction of infectious bacteria with cancer cells has been largely overlooked. We identified that highly metastatic breast cancer MDA-MB-231 cells expressed high level of Toll-like receptor 2 (TLR2) in contrast to poorly metastatic breast cancer cells and homogenous untransformed breast cells. TLR2 in MDA-MB-231 cells were actively triggered by peptidoglycan (PGN) from infectious bacterium Staphylococcus aureus (PGN-SA), resulting in the promoted invasiveness and adhesiveness of the cancer cells in vitro. PGN-SA induced phosphorylation of TAK1 and IkappaB in the TLR2-NF-kappaB pathway of the cancer cells and stimulated IL-6 and TGF-beta secretion in MDA-MB-231 cells. All these effects were abrogated by TLR2 blockade. Further investigation showed that the NF-kappaB, STAT3 and Smad3 activities were augmented sequentially in MDA-MB-231 cells after PGN-SA stimulation. Phosphorylation of NF-kappaBp65 was initially increased and then followed by phosphorylation of STAT3 and Smad3 in the delayed 4 or 6 hours. NF-kappaB inhibition attenuated STAT3 and Smad3 activities whereas PGN-SA-stimulated cell culture supernatants reversed these inhibitory effects. Our study indicated that TLR2 activation by infectious bacterial PGN played an important role in breast cancer cell invasiveness and illustrated a new link between infectious bacteria and the cancer cells, suggesting the importance of antibiotic therapy to treat cancer with bacterial infection.